Depressive symptoms and inflammatory biomarkers in patients with heart failure. (October 2014) - Dekker, Rebecca L; Moser, Debra K; Tovar, Elizabeth G; Chung, Misook L; Heo, Seongkum; Wu, Jia Rong; Dunbar, Sandra B; Pressler, Susan J; Lennie, Terry A
Background: Inflammation may be a link between depressive symptoms and outcomes in patients with heart failure. It is not clear whether inflammatory markers are independently related to depressive symptoms in this population. Aim: To determine which inflammatory biomarkers are independently associated with depressive symptoms in heart failure. Methods and results: We analyzed data from 428 outpatients enrolled in a heart failure registry (32% female, 61 ± 12 years, 48% New York Heart Association Class III/IV). Depressive symptoms were measured with the Beck Depression Inventory-II. Serum C-reactive protein (CRP), cytokines (interleukin 1 receptor antagonist, 2, 4, 6, 8, 10), tumor necrosis alpha, and soluble receptors sTNFR1 and sTNFR2 were measured with enzyme immunoassay. Multiple regressions were used to determine which biomarkers were associated with depressive symptoms controlling for demographics, heart failure severity, and clinical variables. Twenty-seven percent ( n = 119) had depressive symptoms. CRP was related to depressive symptoms after controlling for age and gender, but no inflammatory biomarkers were associated with depressive symptoms after controlling for all variables in the model. Conclusions: There was no relationship between inflammatory biomarkers and depressive symptoms. Our findings, in combination with prior researchers', suggest there is not a robust relationship between depressive symptoms and individual biomarkers of inflammation in heart failure.